Daytime intragastric acid control: post hoc analyses of esomeprazole 20 mg and over-the-counter proton-pump inhibitors. (November 2015) - Katz, Philip; Kahrilas, Peter J.; Johnson, David A.; Lind, Tore; Röhss, Kerstin; Traxler, Barry; Hugo, Vincent; Dent, John
Objectives: In mild gastroesophageal reflux disease, which accounts for the great majority of cases, the major burden of reflux occurs during daytime hours, after food intake. The aim of these analyses was to evaluate intragastric pH control during the typical 14-hour daytime awake period by proton-pump inhibitors (PPIs) given at over-the-counter (OTC) dosages. Methods: In one double-blind and three open-label, randomized, crossover studies, intragastric pH was monitored for 24 hours on day 5 of treatment. The 24-hour data have been reported previously. Post hoc analyses reassessed these studies for the 14-hour daytime period, comparing esomeprazole 20 mg with currently available OTC PPIs omeprazole, pantoprazole (not available in the US) and lansoprazole. Results: Subjects maintained intragastric pH >4 for a significantly greater mean percentage of the 14-hour daytime period with esomeprazole 20 mg compared with any of the PPI comparators at OTC dosages. Geometric mean ratios (95% confidence intervals) for esomeprazole 20 mg versus the comparators were: 1.45 (1.14–1.85; p = 0.003) versus omeprazole 20 mg; 2.50 (2.01–3.11; p < 0.0001) versus pantoprazole 20 mg; and 1.69 (1.46–1.97; p < 0.0001) and 1.89 (1.05–3.37; p = 0.03) versus lansoprazole 15 mg. A greater proportion of subjects had better pH control with esomeprazole than with the other PPIs (range: 69–97%). Conclusions: Across the 14-hour daytime period, esomeprazole 20 mg once daily given 30 minutes before breakfast for 5 days provided acid control for a significantly greater average proportion of time versus the PPI comparators omeprazole, pantoprazole and lansoprazole at currently available OTC dosages.